Using a cultural-ecological framework to explore dietary beliefs and practices during pregnancy and lactation among women in Adivasi communities in the Nilgiris Biosphere Reserve, India. Issue 3 (4th May 2018) - Craig, Hope C.; Jeyanthi, R.; Pelto, Gretel; Willford, Andrew C.; Stoltzfus, Rebecca J.
ABSTRACT: This article explores maternal dietary beliefs and practices gathered through interviews with mothers of infants and young children in Adivasi communities in the Nilgiris Biosphere Reserve, India. Guided by focused ethnographic study methods, interviews were conducted with 33 key informants. We used a cultural-ecological framework to analyze and interpret the texts that were elicited from women about dietary beliefs and eating patterns during pregnancy and lactation. We identify differences between what women were advised to eat, felt they should eat, and reported consuming. The findings offer guidance for interventions to improve maternal diets in this vulnerable population.